Methods of detection of olive oil adulteration - Zadkova, Alexandra; Usatyuk, Svitlana; Korolyuk, Tamara (My University, 2013)
Shows the modern methods of detection of olive oil adulteration.
Keywords: оливкова олія; оливковое масло; оlive oil; фальсифікація; фальсификация; adulteration; фактор автентичності; фактор аутентичности; authenticity factor; кафедра експертизи харчових продуктів